Social media and mindfulness: From the fear of missing out (FOMO) to the joy of missing out (JOMO). Issue 3 (13th August 2022) - Chan, Steven S.; Van Solt, Michelle; Cruz, Ryan E.; Philp, Matthew; Bahl, Shalini; Serin, Nuket; Amaral, Nelson Borges; Schindler, Robert; Bartosiak, Abbey; Kumar, Smriti; Canbulut, Murad
Abstract: Mindless use of social media may lead to negative mental health outcomes for consumers. In this research, the authors focus on the fear of missing out (FOMO) as a key determinant of those negative outcomes by illustrating how repeated social media use forms a habit loop termed "social media FOMO." The authors introduce a "Social Media FOMO to JOMO" framework, where they describe how mindless use can lead to social media FOMO and propose a novel Social Media Mindfulness Practice (SMMP) as a remedy to help consumers reduce FOMO and adopt a path called the joy of missing out (JOMO) that provides greater well‐being. Based on the "Social Media FOMO to JOMO" framework and the SMMP, the authors suggest future research and highlight implications for consumers, marketers, and policy makers to promote more mindful social media use.